Hypercholesterolemia and the role of lipid metabolism gene CES1 in immune infiltration promote central nervous system relapse in acute myeloid leukemia - Bao, Wanwan; Tu, Yansong; Zhang, Shan; Jiang, Xiaoyan; Chen, Huijun; Tu, Huaijun; Li, Jian (Frontiers in Immunology, 2025)
BackgroundAlterations in multiple lipid metabolism pathways are associated with cancer progression. However, the relationship between lipid metabolism and central nervous system (CNS) relapse in acute myeloid leukemia (AML) remains unclear.MethodsWe conducted a retrospective analysis of 806 AML cases to evaluate the association between serum lipid levels and the risk of CNS relapse. Additionally, RNA-sequencing data from 895 AML patients were obtained from the TARGET database to identify hub lipid metabolism-related genes (LMRGs) associated with CNS relapse. In vivo and in vitro experiments were performed to validate the bioinformatics findings.ResultsPatients with CNS relapse exhibited significantly elevated levels of total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) compared to the non-CNS relapse group. Hypercholesterolemia was identified as a risk factor for CNS relapse. RNA sequencing of AML patients with or without CNS relapse revealed 1,368 differentially expressed genes (DEGs). Functional enrichment analysis of the DEGs indicated a connection between lipid metabolism and CNS relapse. Through integrating these DEGs, LMRGs, and whole-genome correlation network analysis (WGCNA), carboxysterase 1 (CES1) was identified as a hub LMRG. High CES1 expression was a risk factor for CNS relapse and shorter overall survival. Moreover, CES1 influenced the proportion of nine types of tumor-infiltrating immune cells (TICs), particularly M2 macrophages, as supported by functional studies involving CES1 knockdown and overexpression in AML cells and AML xenograft tumor models.ConclusionHypercholesterolemia and CES1 can promote CNS relapse in AML patients, particularly through CES1’s potential role in modulating immune infiltration within the TME.